2020
DOI: 10.1098/rsta.2019.0496
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the turbulent kinetic energy budget in an energetic tidal flow from measurements of coupled ADCPs

Abstract: Two coupled four-beam acoustic Doppler current profilers were used to provide simultaneous and independent measurements of the turbulent kinetic energy (TKE) dissipation rate ε and the TKE production rate P over a 36 h long period at a highly energetic tidal energy site in the Alderney Race. The eight-beam arrangement enabled the evaluation of the six components of the Reynolds stress tensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Similar results were documented by Gunawan et al [27]. Nonetheless, our spectra derived from time series of the along-beam velocities exhibit equivalent TKE levels within the inertial subrange, indicating a clear isotropy of the small-scale turbulence (see [13]). In view of this result, we are inclined to think that the anisotropy exhibited in the plot of the spectra associated with the streamwise, spanwise and vertical direction is an artefact of ADCP beam-spreading.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results were documented by Gunawan et al [27]. Nonetheless, our spectra derived from time series of the along-beam velocities exhibit equivalent TKE levels within the inertial subrange, indicating a clear isotropy of the small-scale turbulence (see [13]). In view of this result, we are inclined to think that the anisotropy exhibited in the plot of the spectra associated with the streamwise, spanwise and vertical direction is an artefact of ADCP beam-spreading.…”
Section: Discussionsupporting
confidence: 90%
“…Two upward-looking RDI Workhorse 600 kHz four-beam ADCPs were deployed on the seafloor (mean and maximum water depth of 31 m and 35 m, respectively) approximately 4 km offshore, west of the port of Goury, in the eastern part of Alderney Race, France (figure 1) [13,14]. The instruments were mounted on a specifically designed frame having the following features: 3.3 m long, 2.5 m wide and 2 100 kg weight (figure 1).…”
Section: Data Analysis and Methods (A) Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Rippeth et al (2003) reported values of in the northern Irish Sea with similar ratios near the bed shown by Guerra & Thomson (2017) for Puget Sound, USA. Thiébaut et al (2020) reported ratios ranging between 0.5 and 1.1 at within the Alderney Race in the English Channel. Notably, it was also shown that diffusive transport of turbulent kinetic energy was equal to , thus was considered as a likely source of the local imbalance between production and dissipation.…”
Section: Resultsmentioning
confidence: 99%